Systematic characterization of 3D-printed PCL/β-TCP scaffolds for biomedical devices and bone tissue engineering: Influence of composition and porosity. Issue 14 (15th May 2018) - Bruyas, Arnaud; Lou, Frank; Stahl, Alexander M.; Gardner, Michael; Maloney, William; Goodman, Stuart; Yang, Yunzhi Peter
Abstract: Abstract : This work aims at providing guidance through systematic experimental characterization for the design of 3D-printed scaffolds for potential orthopedic applications, focusing on fused deposition modeling with a composite of clinically available polycaprolactone (PCL) and β-tricalcium phosphate (β-TCP). First, we studied the effect of the chemical composition (0–60% β-TCP/PCL) on the scaffold's properties. We showed that surface roughness and contact angle were, respectively, proportional and inversely proportional to the amount of β-TCP and that degradation rate increased with the amount of ceramic. Biologically, the addition of β-TCP enhanced proliferation and osteogenic differentiation of C3H10. Second, we systematically investigated the effect of the composition and the porosity on the 3D-printed scaffold mechanical properties. Both an increasing amount of β-TCP and a decreasing porosity augmented the apparent Young's modulus of the 3D-printed scaffolds. Third, as a proof of concept, a novel multimaterial biomimetic implant was designed and fabricated for potential disc replacement.